Management and Development of Productive Salt Pond Waqf in Galis District Pamekasan Regency - Ainol Yakin; Abdullah Faqih Salam (Mabny: Journal of Sharia Management and Business, 2026)
Purpose - Research on productive waqf has generally focused more on the management of waqf assets in the form of land, agriculture, property, education, and trading businesses. Methodology - The approach used in this study is a qualitative approach. A qualitative approach is a type of research that uses a natural setting with the aim of interpreting phenomena that occur and is conducted by involving various existing methods. Findings - The results of this study are as follows: 1) The management of productive waqf salt ponds has been implemented but is not yet optimal, 2) Productive waqf salt ponds provide economic benefits to the community,there are various obstacles in the development of productive waqf salt ponds, 3) community participation is an important factor in the success of management,the development of productive waqf requires more innovative strategies. Implications - The implication of this study are the implementation of waqf salt pond management by nadzir and the community, an increase in the economic activities of coastal communities, fluctuations in production results due to weather and seasonal factors, limitations in facilities and salt production technology,the utilization of waqf proceeds for social and religious purposes, and efforts to develop and improve the management system. Originality - The novelty of the research focus on the management of productive waqf based on salt ponds as an economic asset for coastal communities.